Effectiveness of human resources management in the enterprises of Ukraine’s bakery industry - Yuryk, Yaryna; Bezpalko, Olena; Hryniuk, Julia (My University, 2021)
Competition in the national labor market, which is strengthening as globalization and structural employment disproportions intensify, encourages domestic companies to seek reserves for more effective human resource management as the only competitive advantage that cannot be copied. The aim of the research is to develop a comprehensive methodology for assessing the effectiveness of HR management at bakery companies as employers of a Ukraine’s priority industry, which is based on the provisions of the new (first) international human capital accounting standard ISO 30414:2018 and is implemented using system-structural, abstract-logical methods, as well as those of multidimensional statistical analysis and visualization of empirical data. The developed methodology will allow to determine an integrated indicator for the effectiveness of HR-management, which simultaneously performs the functions of controller and navigator of strategic management decisions in this area.
Keywords: управління персоналом; ринок праці; людський капітал; human capital; таксономія; labor market; personnel management; кафедра економіки праці та менеджменту